Optimizing In Vitro Propagation of Haworthia truncata Schönland Using Leaf, Root, and Inflorescence - Leila Soleimani; Hassan Salehi; Taras Pasternak (Plants)
Haworthia truncata, a species native to South Africa, is characterized by its limited growth and scarcity, contributing to high production costs. Countries like China and Turkey are known for exporting Haworthia globally. Tissue culture offers an efficient method for mass-producing unique and beautiful species such as H. truncata. This study tested Murashige and Skoog (MS) basal media supplemented with various concentrations of IBA (0.05–1.5 mg/L), NAA (0.05–0.25 mg/L), and BA (0.25–1.5 mg/L) to promote shoot proliferation. MS medium without plant growth regulators (PGRs) was also tested as a control. Different explant types (leaf, root, and inflorescence) were analyzed for their potential in direct and indirect regeneration. Inflorescence explants showed the highest callus induction with 1.5 mg/L IBA, while optimal shoot proliferation occurred at 1 mg/L IBA. Callus induction was optimal for leaf explants with 0.05 mg/L NAA and 0.25 mg/L BA, and shoot proliferation was highest at 0.05 mg/L NAA and 1 mg/L BA. Root explants achieved maximum callus induction with 0.25 mg/L BA and 0.25 mg/L NAA, with the best shoot proliferation using 0.05 mg/L NAA and 1 mg/L BA. The highest rooting percentage of regenerated shoots was obtained on ½ MS medium with 1.5 mg/L IBA.